Immoral costumes (Revista de Ensino em Artes, Moda e Design, 2021)
This article analysis the costumes of the performance “A Public Cervix Anouncement” (1990) by Annie Sprinkle (USA) and the plays “Manga Rosa” (2015) by Lua Menezes from Bololô Cia. Cênica (RN/Brazil) and “Stabat Mater” (2019) by Janaína Leite (SP/Brazil), considering how the appearances of the bodies are presented on stage and how they dialogue and tension the judgments and violences concerning the women’s body, arising from moral vigilances. The choices for these pieces were by their aesthetic similarities in their costumes designs, in the pieces of clothes that they present, in the exposition of the body parts and in their dialogue with themes such as erotism, intimacy and autobiography. Besides that, it’s importante to highlight that these three artists in scene are white, cisgender and western women, so, they elaborate the women’s body related to their social and subjective experiences and it does not universalize the experience of being a woman in a society.
Keywords: Costumes design; Morality; Gender